Analysis of Factors Affecting Customer Satisfaction at PT.OSO Gallery - Karendita Dayri Prawira; B. P. Kusumo Bintoro; Rachmat Hadis; Warseno Warseno; Yochebed Anggraini Terah (ADI Journal on Recent Innovation, 2022)
This study aims to identify factors affecting costumer satisfaction in PT.OSO sekuritas cabang galeri Universitas MH. Thamrin and describe it based on customer perceptions. This research uses qualitative approach with case study strategy. Data collection techniques used are interviews, observation, and document review. The participants of this study 25 customer with different background (student or employee). The result of study shows that factors affecting costumer satisfaction in PT.OSO sekuritas cabang galeri Universitas MH. Thamrin Branch are the excellent of the relationship between the employee and the costume, accurancy in satisfying customer desires or demand and adequate facilities in the investment gallery. This strategy will always improved by the employees to provide customer satisfaction in the long term.